Epistemological decolonization and political education in Colombia. Towards a citizen perspective of «buen vivir» (Foro de Educacion, 2020)
This article, that starts from the theoretical review made within the development of a doctoral thesis, aims to analyze the contribution that epistemological decolonization can make to the necessary transformations in the Colombian educational system, taking as an example political or citizen education. For this, the most important concepts in the classical epistemological discussion are reviewed initially with the approaches of Karl Popper, Thomas Kuhn, Paul Feyerabend and the Critical Theory. Then, the main postulates of the decolonial theories and the southern epistemologies are presented, their central concepts, representative authors and contributions to the epistemological discussion to, subsequently, review the experiences and theoretical foundations of pedagogical currents that are part of this trend, addressing the principles of Buen Vivir and Vivir Bien, from which the proposal of citizen education in Colombia is analyzed critically. Finally, it is concluded that a process of epistemological decolonization, based on the principles of Buen Vivir, is necessary, not only for political education, but also for the education system in general, in the search for new forms of education, based on the respect for all forms of life, respect for others and towards nature.